The Pandemic and Beyond: Innovation in Cardiovascular Training to Improve Quality of Education and Trainees’ Well-being - Hyeon-Ju R. Ali; Stephen H. Little; Nadeen N. Faza (Methodist DeBakey Cardiovascular Journal)
During the first 2 years of the coronavirus-19 pandemic, many changes and innovations occurred to overcome the challenges associated with the pandemic and improve cardiovascular training. This review highlights the literature on the pandemic response regarding cardiovascular fellowship education and identifies areas of need to ensure future opportunities for fellows to achieve competency and career advancement. Specifically, we describe the recent changes to the four cornerstones of cardiovascular training: core content education, procedural training, career development, and the well-being of trainees.